Counter-Human Trafficking in East Nusa Tenggara: The Urgency of Strengthening NGOs Role through Multilevel Collaborative Governance - Arie Kusuma Paksi; Amalia Nurul Hutami (Jurnal Ilmiah Hubungan Internasional, 2023)
Human trafficking has been one of the prolonged transnational organized crime issues in Indonesia, especially in East Nusa Tenggara Province (NTT). Though government has made some efforts to address the issue, the trafficking cases in the region still remains high. This research attempts to analyze and challenge the existing anti-trafficking scheme designed and performed by the government. Using a qualitative research method, this research found that the government has managed to include non-state stakeholders—such as NGOs and civil society organizations—in its counter trafficking strategy. However, the role of non-state stakeholders are still limited and regarded as a mere technical support as well as an assistance provider for the trafficking victims, rather than engaged in an early and further strategic stage. The established cooperation tends to represent a partnership instead of a collaboration. This research highlights the urgency of redesigning counter-trafficking response in East Nusa Tenggara and strengthening the role NGOs through a collaborative multilevel governance, which emphasize further engagement of non-state stakeholder in policy-making process. Keywords: Human trafficking; NGOs role; multilevel collaborative governance.